Inclusive School Management at Susukan 04 State Elementary School - Matius Kurniawan; AY Soegeng Ysh; Ngurah Ayu Nyoman Murniati (Journal of Educational Sciences, 2026)
This study aims to analyze the management of inclusive schools at Susukan 04 State Elementary School. The study used a qualitative case study approach, with data collection techniques through in-depth interviews, participatory observation, and document review. Data analysis used the Miles & Huberman model. The results of the study indicate that the management of inclusive schools at SD Negeri Susukan 04 has been running well. The management process is carried out through the stages of goal planning, preparation of work programs and budgeting RKS and RKAS, team formation and clear division of tasks, and effective resource management. Implementation is focused on modifying the curriculum at each grade level, considering the distribution of PDBK. Implementation is supported by close collaboration between class teachers and GPK (Special Guidance Teachers), as well as partnerships with external parties such as therapists and psychologists. Supervision is carried out in a structured and systematic manner, supported by instruments and follow-up. Overall, it is concluded that Susukan 04 State Elementary School has implemented a comprehensive inclusive school management model from planning to supervision well, even though there are challenges that accompany.